Konsentrasi pencemar timbal (Pb) pada sayur lalapan di pasar tradisional dan supermarket di Kota Yogyakarta - Tamariska Sharon Christa Bella; Djoko Rahardjo; Kisworo Kisworo (Sanitasi: Jurnal Kesehatan Lingkungan, 2023)
Lalapan is a popular food consumed. The increase in population, industrial activities, transportation, use of chemical fertilizers and pesticides has led to lead (Pb) pollution in the environment, contaminating vegetables that are to be consumed and posing health risks. Therefore, research was conducted regarding the analysis of Pb pollutant concentrations in lettuce, basil and cucumber sold in traditional markets and supermarkets in the city of Yogyakarta. Samples were extracted using 65% HNO3 and 37% HCl, and then the concentration of Pb in the samples was analyzed using Atomic Absorption Spectrophotometry. The research results showed that all types of vegetables sold in traditional markets and supermarkets have been contaminated with Pb with concentrations ranging from 0.418 to 1.575 mg/kg, with the highest Pb concentration was found in basil with an average of 1.5156 mg/kg. The average concentrations of Pb in lalapan sold in traditional markets and supermarkets, when compared to the quality standard set by SNI regulation (2009) for cucumber sold in supermarkets N, are still below the safe limit of 0.5 mg/kg for , while the rest have exceeded the quality standard limit. There are significant differences in the concentration of Pb pollutants in vegetables sold in markets and supermarkets, as well as based on sales location, type of vegetable, and vegetable source. The consumption pattern of vegetables ranges from 62-97 g/day and poses health risks as the RQ value is greater than 1. Additionally, it has the potential to cause cancer because ECR > E-4.